Предмет: Алгебра, автор: namelaim2

Допоможіть розв'язати

Приложения:

Ответы

Автор ответа: Universalka
1

\displaystyle\bf\\\frac{Sin\Big(\pi -\alpha \Big)Sin\Big(\alpha +2\pi \Big)}{tg\Big(\pi +\alpha \Big)Cos\Big(\dfrac{\pi }{2} +\alpha \Big)} =\frac{Sin\alpha \cdot Sin\alpha }{tg\alpha \cdot(-Sin\alpha )} =-\frac{Sin\alpha }{tg\alpha } =\\\\\\=-\frac{Sin\alpha }{\frac{Sin\alpha }{Cos\alpha } } =-\frac{Sin\alpha \cdot Cos\alpha }{Sin\alpha } =-Cos\alpha \\\\\\-Cos\alpha =-Cos\alpha

Тождество доказано

Похожие вопросы
Предмет: Алгебра, автор: Ksyha1288